2022
DOI: 10.3389/fimmu.2022.904682
|View full text |Cite
|
Sign up to set email alerts
|

Risk, Incidence, and Mortality of Breast Cancer in Primary Sjögren’s Syndrome: A Systematic Review and Meta-Analysis

Abstract: BackgroundPrimary Sjögren’s syndrome (pSS) and breast cancer are a highly prevalent autoimmune disease and malignancy, respectively, both occurring predominantly in females. Whether there is a link between these two diseases is uncertain. We conducted a systematic review and meta-analysis to investigate the risk, incidence, and mortality of breast cancer in patients with pSS.MethodsWe systematically searched Embase, PubMed, and Web of Science on January 31, 2022 to identify the study that assessed risk, incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Our results appear to be similar to those in some recent reports and consistent with the increased risk of BC in the Asian population of Sjögren's syndrome. [33,35] In this study, we revealed the strong association of DM with the increased risk of BC with a high OR of 10.4 in pSS. DM itself seems to be not associated with the increased risk of BC in the general population in Taiwan as previously reported in a previous nationwide population study, although the association of DM with BC with low OR had been reported in some studies.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Our results appear to be similar to those in some recent reports and consistent with the increased risk of BC in the Asian population of Sjögren's syndrome. [33,35] In this study, we revealed the strong association of DM with the increased risk of BC with a high OR of 10.4 in pSS. DM itself seems to be not associated with the increased risk of BC in the general population in Taiwan as previously reported in a previous nationwide population study, although the association of DM with BC with low OR had been reported in some studies.…”
Section: Discussionsupporting
confidence: 51%
“…Indeed, some previous studies reported the different results on the association of autoimmune diseases with the risk of BC, and it seems that there are geographical differences in the association of Sjögren’s syndrome with the risk of BC. [28–33] In this study, we found that the prevalence of BC in pSS patient was 3900 per 100,000 persons, which appears to be much higher than 834.37 per 100,000 persons of the female general population in Taiwan in 2013. [34] The incidence rate of 650 per 100,000 person-years for BC in pSS patients was also higher than that of 93.00 per 100,000 person-years for BC of the female general population in 2013 in Taiwan.…”
Section: Discussionmentioning
confidence: 77%
“…However, we also found an inverted U-shaped relationship between CRP and breast cancer. The inverse association between CRP and breast cancer in the extremely high group could possibly be explained by the inverse association between breast cancer and autoimmune disease [ 33 , 34 ], as these patients were characterized by high levels of CRP.…”
Section: Discussionmentioning
confidence: 99%
“…Sjögren's syndrome (SS) is a chronic systemic autoimmune disease, which has been reported associated with various cancers, such as lymphoma [49,50], B-cell non-Hodgkin lymphoma [51], extranodal marginal zone lymphoma [52][53][54], follicular dendritic cell sarcoma [55], breast cancer [32], diffuse large B-Cell lymphoma[56, 57], ovarian cancer [34], multiple myeloma [35], tongue cancer [35], thyroid cancer[58], cancers of the lip and oral cavity[58], and stomach cancer[58], etc. Although several epidemiological researchers have mentioned the link between SS and cancer risks, it was di cult to certify the causality of SS on cancer risks based purely on epidemiological or association studies.…”
Section: Discussionmentioning
confidence: 99%
“…Krishna C Thandra et al revealed that Non-Hodgins's lymphoma is strongly associated with SS [31]. Previous researchers found that patients with SS had an elevated risk of breast cancer in Asian countries and Argentina [32]. Radjiv Goulabchand et al [33] found that there was an increased risk of hematological malignancies and thyroid tumors in patients with SS.…”
Section: Introductionmentioning
confidence: 99%